Utilización de materiales didácticos innovadores dirigidos a la enseñanza de las matemáticas a los Octavos años de Educación Básica de la Unidad Educativa “Sara Serrano de Maridueña” de Puerto Bolívar, en el periodo lectivo 2013-2014. - Bermeo Quishpe, Leonor Priscila (2014)
The development of this thesis : Use of innovative teaching materials aimed at teaching math to eighth years of Basic Education of the Education Unit " Sara Serrano Maridueña " of Puerto Bolivar in the 2013-2014 academic year , is diagnostic work in a research - oriented purposeful determine how this affects the use of innovative teaching materials in the teaching of mathematics in the eighth year of basic education ; for which a methodological process based on inductive , deductive , descriptive statistical methods and hypothetical , the same as those supported in the techniques of observation, interviews , surveys and signing took place .